93.3k views
3 votes
Substitute the value of x back into the equation x + 3 – 2x = + x + 5 to justify the solution. What value of x is the solution?

Edit: 
Just solved it, 

it's -1.

User Otc
by
6.1k points

2 Answers

3 votes

Answer:

-1 good luck guys

Explanation:

User Tysonwright
by
5.4k points
5 votes
For this case we have the following equation:

x + 3 - 2x = x + 5
The first thing we must do is to group similar terms.
To do this, we write the variables on one side of the equation and the constants on the other side of the equation.
We have then:

x - 2x - x = 5 - 3
Rewriting both sides of the equation we have:

-2x = 2
When clearing x we have:

x = (2) / (- 2) x = -1
Answer:
The value of x that is solution of the equation is:
x = -1
User Dennis Guse
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.